Implementation of the Project Based Learning (PJBL) Atmospheric Material Learning Model to Improve Students' Cognitive Abilities in the Era of Independent Learning - Lailiiyah, Nur; Zain, Ita Mardiani (JUPE : Jurnal Pendidikan Mandala, 2024)
This research aim to determine the effectiveness of Project Based Learning or PjBL learning model wichis the output is integrated maket and website via barcode to improving student’s cognitive abilities on atmospheric subject in the era of independent learning which is related with kodrat alam and kodrat zaman concept in kurikulum merdeka. This research used the Classroom Action Research or PTK method. Data was obtained through pretest and postest before and after PTK done, then data analysis was carried out using Wilcoxon Signed Ranks. Based on the data processed Sig. (2-tailed) or P value is 0.000, so that value <5%. Based on theory, Sig. (2-tailed) or P value <5% is decided to accept Hi, then Ho is rejected. So, there is a difference average pretest and postest score, the meaning of that difference is increasing student’s cognitive values in this learning that using the PjBL learning model wichis the output is integrated maket and website via barcode on atmospheric subject in the era of independent learning or kurikulum merdeka.